EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DENGAN GUIDED DISCOVERY LEARNING PADA MATERI BANGUN RUANG SISI DATAR DITINJAU DARI LOCUS OF CONTROL - Widodo, Widodo; Sujadi, Imam; Riyadi, Riyadi (Jurnal Pembelajaran Matematika, 2015)
Abstract: The aims of the research were to determine the effect of learning models on learning achievement viewed from the students locus of control (LOC). The learning models compared were Jigsaw by using Guided Discovery Learning (GDL), jigsaw and direct learning. The type of this research were aquasi-experimental research with the factorial design 3x3. The population were the students of the VIII class of SMP Negeri Ponorogo Regency in the academic year of 2013/2014. The samples of the research consisted of 263 students and were taken through stratified cluster random sampling. The proposed hypothesis of the research were tested by using the two-way analysis of variance with unbalanced cells. The conclusions of this research were as follows. (1) Jigsaw-GDL provided better learning achievement than jigsaw and direct instruction, while jigsaw provided better learning achievement than direct instruction, (2) the students with high LOC had better learning achievement than medium and low LOC, students with medium LOC had better learning achievement than low LOC, (3) in students with high LOC, the use of jigsaw-GDL provided learning achievement as good as jigsaw, the use of Jigsaw provided learning achievement as good as direct instruction, the use of Jigsaw-GDL provided the better learning achievement than direct instruction, in students with medium and low LOC, there were no difference in learning achievement in each learning model, (4) in Jigsaw-GDL learning model, there were no difference in learning achievement between students with high LOC and medium LOC, and both of them had better learning achievement than students with low LOC, in Jigsaw and direct learning model, there were no difference in learning achievement in each level of LOC.Keywords: Jigsaw-GDL, Jigsaw, Locus of Control, and Learning Achievement